Analysis Of The Impact Of The Use Of Digital Financial Information Systems In The Finance & Accounting Division At PT Finnet Indonesia - Adira Ferdiansyah Chaniago; Katiya Nahda (Cita konsultindo, 2025)
This study aims to analyze the impact of utilizing the Finpay digital financial information system on the performance of the Finance & Accounting Division at PT Finnet Indonesia. Employing a descriptive qualitative approach with a case study method, this research collected primary data through observations during an internship from February to June 2023 and semi-structured interviews with six respondents in August 2025, as well as secondary data from internal company documents and academic literature. The Technology Acceptance Model (TAM) framework was used to analyze perceived usefulness and perceived ease of use. The findings indicate that the Finpay system enhances operational efficiency, data recording accuracy, and transparency through the automation of transaction and financial reporting processes in real-time. This study provides practical insights for PT Finnet Indonesia to optimize digital transformation in the financial sector.